İŞYÜKÜ FAZLALIĞININ YAŞAM KALİTESİ ÜZERİNDEKİ ETKİSİNDE İŞ- AİLE ÇATIŞMASININ ARACI ROLÜ: SAĞLIK SEKTÖRÜNDE BİR UYGULAMA - Korkmazer, Fuat; Aksoy, Ali (My University, 2020)
Bu çalışmada, iş yükü fazlalığı algısının yaşam kalitesi üzerindeki etkisinde iş- aile çatışmasının aracı rolünün ortaya konulması amaçlanmıştır. Bu çalışmanın konusu belirlenirken, ilgili değişkenlerin çalışanların motivasyonuna olumlu katkı sağlayacak şekilde dengeli olması gerektiği gerçekliğinden hareket edilmiştir. Bu amaçla TRB-2 bölgesindeki (Van, Muş, Bitlis, Hakkâri) Sağlık Bakanlığı’na bağlı devlet hastanelerinde çalışanlara bir anket uygulanmıştır. Anket, İş Yükü Fazlalığı Ölçeği, WHOQOL-BREF-TR Yaşam Kalitesi Ölçeği ve İş-Aile Çatışması ölçeklerinden oluşmaktadır. Elde edilen veriler, yapısal eşitlik modeli (YEM) ve karşılaştırmalı istatistiki analizlere tabi tutularak yorumlanmıştır. Yapılan YEM analizi sonucuna göre iş yükü fazlalığı algısının, yaşam kalitesini negatif yönde çok düşük düzeyde etkilediği, işten aileye çatışma ve aileden işe çatışmayı pozitif yönde etkilediği sonucuna ulaşılmıştır. İşten aileye ve aileden işe çatışmanın ise yaşam kalitesini negatif yönde etkilediği sonucuna ulaşılmıştır.

1. LITERATURE 1.1. RESEARCH SUBJECT The study, which covers a significant part of daily time, is important because it leads the life of the individual and his family. Therefore, emotions, meanings and values for the study gain importance. In the life of people, the bonds outside of work are continuing with family, friends, relatives and non-governmental organizations. While establishing these ties, the most important issue is the relations with people's families. For this reason, people's expectations regarding life are related to the jobs they spend most of their daily lives or their families. The perception of the individual that the work undertaken at the institution where he works is above the normal is called workload. For most jobs, it is possible to say that this concept has abstract content based on perception (if the natural burden of the work is not calculated) (Keser, 2006). Workload excess is an imperative that an individual performs more than he / she can do in the normal timeframe and with his talents (Yüksel 2003). One of the leading problems of today's business 1996). world is the conflicts between family and work. The fact that the individual's work is intense affects family lives negatively and reduces both his happiness and his family's happiness. Giving importance to the job neglects the family or giving importance to the family results in neglect of the job. Today, as a result of rapid developments in the field of medicine, it is aimed to increase the quality of life of individuals. In line with this goal, there is an increasing effort to measure the quality of life and wellbeing (Yıldırım & Hacıhasanoğlu, 2011). In measuring health well-being, the concept of quality of life has been developed, which shows the level of the individual's functional status (Testa and Simonson, The Theory of Conservation of Resources (COR) is an approach that may be useful in understanding the impact of workload excess on quality of life and work-family conflict levels (Hobfoll, 1989). According to the theory, the resources that are valuable for individuals are categorized in four groups. These resources are: material resources, conditions, personal characteristics and energy (Hobfoll, 1989). According to this theory; individuals strive to obtain, protect and increase the resources they value. Because as the personal characteristics and social conditions of individuals are improved and protected, the aim is to achieve a successful life for them. Environmental conditions often pose a threat to these resources or cause resources to decrease. This threat is important for individuals because of the values of the resources. In other words, the resources that the person struggles to obtain, protect and increase are valuable both because of the features they possess and the opportunity to obtain new resources for the person (Yurur, 2011). Since life is a whole, it is not possible to consider working and living conditions, therefore, work and quality of life separate. This is due to the close interaction between work and living conditions (Schulze 1998). Health workers are satisfied with their profession as they help people in need of health services, and this satisfaction ensures that the employee experiences job satisfaction. As a result of the employees feeling themselves as part of the workplace, it is possible that they improve positively in performance and work efficiency, with increased job satisfaction. 1.2. RESEARCH PURPOSE AND IMPORTANCE In the professions that directly serve people, the human element has an important place in the quality of the service. Low quality of life is more common in these professions, which are worked face to face with people (Barron, West 2007; Kaçmaz 2005). The low quality of life in healthcare workers, workload density, care given to severe patients, relationship and distribution of duties at work, disturbed sleep patterns, night bouts, and dealing with relatives (French et al., 2000; Kaçmaz 2005). Examining the workload and working conditions of health workers is very important in terms of the quality of life of the employees and the quality of the services provided. It is very important to eliminate the problems related to the working conditions of the employees and to increase their quality of life, in order to i
THE MEDIATING ROLE OF WORK- FAMILY CONFLICT ON THE EFFECT OF WORKLOAD OVERVIEW ON THE QUALITY OF LIFE: AN IMPLEMENTATION IN THE HEALTH SECTOR